Algorithm‐based direct power control of active front‐end rectifiers. Issue 4 (6th February 2019) - Kumar, Amit; Srungavarapu, Gopalakrishna
Abstract : Switching Table‐based Direct Power Control (ST‐DPC) is one of the most widely used techniques in Active Front‐End (AFE) rectifiers. Proper control of switching states of the power converter is essential to obtain better power quality performance and quicker response to the load demand. In the classical ST‐DPC techniques such as Virtual Flux with Noguchi's Table‐based DPC (VF‐NT‐DPC) and Virtual Flux with Improved Table‐based DPC (VF‐IT‐DPC) etc., these switching states are decided based on a predefined static switching table. Hence, they have poor power quality and dynamic performance with load variations. In this research work, in‐depth mathematical analysis is carried out based on the quantised values of 'the rate of change of active and reactive powers' and an algorithm is introduced for AFEs. Since, the proposed algorithm is considering the quantised values of 'the rate of change of active and reactive powers', which is dynamic in nature; therefore, it has reduced THD, lesser power ripple, and quicker response than classical ST‐DPC techniques. To show the superiority of the Algorithm based DPC (A‐DPC) technique experimental work is carried out and the power quality performance of the proposed A‐DPC is compared with conventional ST‐DPC techniques VF‐NT‐DPC and VF‐IT‐DPC.